2010
DOI: 10.4081/gh.2010.182
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Health Insurance Portability and Accountability Act privacy rule on influenza research using geographical information systems

Abstract: Abstract. The Health Insurance Portability and Accountability Act (HIPAA) privacy rule was enacted to protect patients' personal health information from undue disclosure. Despite its intention to protect patients, recent reports suggest that HIPAA restrictions may be negatively impacting health research. Quantitative, visual geographical and statistical analysis of zip code geographical information systems (GIS) mapping, comparing 3-digit HIPAA-compliant and 5-digit HIPAA-non-compliant simulated data, was chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…At the same time, the difference in spatial resolution between the 2 forms of zip codes carries potentially problematic costs. For instance, one study demonstrated how different disease patterns emerge depending on whether 3-digit or 5-digit zip code areas are used, and with an example data set, the authors showed that if 3-digit zip code areas are used to determine how to best distribute N95 respirators during a pandemic, it would result in a surplus of supplies for health care workers in some communities and shortages others [ 30 ].…”
Section: Twin Challenge 1: Ambiguitymentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the difference in spatial resolution between the 2 forms of zip codes carries potentially problematic costs. For instance, one study demonstrated how different disease patterns emerge depending on whether 3-digit or 5-digit zip code areas are used, and with an example data set, the authors showed that if 3-digit zip code areas are used to determine how to best distribute N95 respirators during a pandemic, it would result in a surplus of supplies for health care workers in some communities and shortages others [ 30 ].…”
Section: Twin Challenge 1: Ambiguitymentioning
confidence: 99%
“…These differences are not hypothetical as relevant examples are abundant in the literature. Bearing in mind that researchers rarely describe their decision-making in detail, there is a body of work that seems to operate under the 3-digit zip code interpretation [8,10,17,[27][28][29][30]. Another realm of scholarship appears to operate under the 5-digit zip code interpretation [4,26,30], and there is related work that seems to suggest the capability of aggregating any geocode to meet the 20,000 threshold [7,8,25].…”
Section: Drivers and Implications Of The 2 Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies discussed mental retardation in children (1.7%) (Zhen et al, 2008(Zhen et al, , 2009), influenza and pneumonia (1.7%) (Crighton et al, 2008;Tellman et al, 2010), child mortality (1.3%) (Kazembe et al, 2007;Sartorius et al, 2011), meningococcal disease (0.9%) (Maïnassara et al, 2010), conjunctive-uveal granuloma (0.9%) (Jayakumar et al, 2009), alcohol outlet density and alcohol consumption (0.9%) (Schonlau et al, 2008) and, finally, one descriptive epidemiological study with no clear disease or risk factor emphasis (Catelan and Biggeri, 2010).…”
Section: Diseases Injuries and Risk Factorsmentioning
confidence: 99%